Factors impacting the transition to adulthood of youth with fragile X syndrome and their families: Facilitators, obstacles and needs. (August 2020) - Gauthier-Boudreault, Camille; Gallagher, Frances; Trépanier, Jordane; Corbin, Francois; Couture, Mélanie
Abstract: Background: The transition from school to adulthood is a critical time for families of youth with disabilities. Few studies have focused on the needs of families of youths with fragile X syndrome. This syndrome is often associated with intellectual disability and autism spectrum disorder, which creates specific needs that must be documented to improve transition planning. The aim of the current study was to document factors impacting transition planning and describe parents' experiences during this period. Method: Individual interviews were conducted with thirteen parents of young people with fragile X syndrome. Two research team members analysed the interviews separately. Results: Factors related to the youth, the youth's family and the steps taken by the various institutions involved during this period seem to impact this transition and contributed to families' anxiety. A clear, uniform transition planning process, initiated early enough to have time for exploratory work placements, and gradual integration emerged as crucial facilitators for the parents in this study. Conclusions: Understanding the reality of people with fragile X syndrome and their families will help to adapt services and develop concrete plans for their future.